A JWST Medium-resolution MIRI Spectrum and Models of the Type Ia Supernova 2021aefx at +415 days - C. Ashall; P. Hoeflich; E. Baron; M. Shahbandeh; J. M. DerKacy; K. Medler; B. J. Shappee; M. A. Tucker; E. Fereidouni; T. Mera; J. Andrews; D. Baade; et al. (The Astrophysical Journal, 2024)
We present a JWST MIRI medium-resolution spectrometer spectrum (5–27 μ m) of the Type Ia supernova (SN Ia) SN 2021aefx at +415 days past B -band maximum. The spectrum, which was obtained during the iron-dominated nebular phase, has been analyzed in combination with previous JWST observations of SN 2021aefx to provide the first JWST time series analysis of an SN Ia. We find that the temporal evolution of the [Co iii ] 11.888 μ m feature directly traces the decay of ^56 Co. The spectra, line profiles, and their evolution are analyzed with off-center delayed-detonation models. Best fits were obtained with white dwarf (WD) central densities of ρ _c = 0.9−1.1 × 10 ^9 g cm ^−3 , a WD mass of M _WD = 1.33–1.35 M _⊙ , a WD magnetic field of ≈10 ^6 G, and an off-center deflagration-to-detonation transition at ≈0.5 M _⊙ seen opposite to the line of sight of the observer (−30°). The inner electron capture core is dominated by energy deposition from γ -rays, whereas a broader region is dominated by positron deposition, placing SN 2021aefx at +415 days in the transitional phase of the evolution to the positron-dominated regime. The formerly “flat-tilted” profile at 9 μ m now has a significant contribution from [Ni iv ], [Fe ii ], and [Fe iii ] and less from [Ar iii ], which alters the shape of the feature as positrons mostly excite the low-velocity Ar. Overall, the strength of the stable Ni features in the spectrum is dominated by positron transport rather than the Ni mass. Based on multidimensional models, our analysis is consistent with a single-spot, close-to-central ignition with an indication of a preexisting turbulent velocity field and excludes a multiple-spot, off-center ignition.